2019
DOI: 10.21037/tcr.2019.06.02
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopy versus open approach in patients with Masaoka stage III thymic epithelial tumors

Abstract: Background The treatment options for Masaoka stage III thymic epithelial tumors are diverse, mainly because the lesions infiltrate the neighboring organs, major vascular structures, with different scopes, extents, and manners. Surgical treatment is the main treatment for the patient in this stage. However, for minimally invasive or open surgery, the current controversy remains large. This study aimed to investigate the feasibility and indications of minimally invasive resection in the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Soder and co‐workers [22] retrospectively analyzed a monocentric 20‐year experience in thymic surgery comparing open and robotic approach: They find a significant reduction in PC in the robotic group (6.8% versus 21.1%) despite a significant greater proportion of extended resections in the robotic group after a propensity score match. Conversely, in a small retrospective study, Chen [23] compared VATS and open surgery in the treatment of Masaoka stage III thymomas and they found that phrenic nerve and vena cava resection was more likely to be performed by open surgery rather than VATS. Nonetheless, in the vast majority of reported experiences, complex extended resections are performed by open sternotomy, thoracotomy or clamshell incision [3, 9, 21, 24, 25].…”
Section: Commentmentioning
confidence: 99%
“…Soder and co‐workers [22] retrospectively analyzed a monocentric 20‐year experience in thymic surgery comparing open and robotic approach: They find a significant reduction in PC in the robotic group (6.8% versus 21.1%) despite a significant greater proportion of extended resections in the robotic group after a propensity score match. Conversely, in a small retrospective study, Chen [23] compared VATS and open surgery in the treatment of Masaoka stage III thymomas and they found that phrenic nerve and vena cava resection was more likely to be performed by open surgery rather than VATS. Nonetheless, in the vast majority of reported experiences, complex extended resections are performed by open sternotomy, thoracotomy or clamshell incision [3, 9, 21, 24, 25].…”
Section: Commentmentioning
confidence: 99%
“…However, the Masaoka system is a surgical-pathologic staging system which is de ned after surgical resection, and no agreement has been reached to de ne the clinical stage before surgery in TETs at present. Although empiric evidence has led surgical resection to be the predominant therapy in TETs and complete resection is a consistent prognostic factor [10][11][12] , still some patients with high-risk thymomas and thymic carcinomas are hardly to receive complete resection and need multimodal therapy approaches including neoadjuvant chemotherapy or radiotherapy 13 .…”
Section: Introductionmentioning
confidence: 99%